THE INFLUENCE OF PROFITABILITY RATIO, LIQUIDITY, CAPITAL STRUCTURE AND FIRM SIZE ON COMPANY VALUE IN BANKING COMPANIES LISTED ON THE BEI FOR THE 2018-2022 PERIOD - Desy Nurul Mawaddah; Rico Nur Ilham; Darmawati Muchtar; Wahyuddin (PT. Radja Intercontinental Publishing, 2024)
Banking companies are an economic sector that operates in the financial sector and has an important role, namely providing and channeling funds for community economic development. Banks are business entities that collect funds from the public in the form of savings and distribute them to the public in the form of credit or other forms in order to improve the standard of living of many people. This research is to examine the influence of Profitability (ROA), Liquidity (CR), Capital Structure (DER) and Firm Size (SIZE) on Company Value (PER) in banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Research data can be accessed on the official websites www.idx.co.id, www.britama.com and www.finance.yahoo.com. The sample in this research consisted of 31 companies. The data analysis tool in this research uses the Panel Data Regression method with the Eviews 10 application tool. The research results found that ROA had a positive and insignificant effect on (PER), CR had a negative and insignificant effect on (PER), DER had a negative and significant effect. on (PER) and SIZE have a positive and insignificant effect on (PER).